RHETORICAL ANALYSIS OF BUSINESS STUDENTS WRITING: A RESEARCH PAPER - Ahmad Idris Asmaradhani (Universitas Muhammadiyah Surabaya, 2007)
ABSTRACIt has always been recognized that when a speaker wishes to persuade, he or she must analyze the speech situation and adapt his or her speech to it. In numerous discussions about rhetoric, Aristotle is recognized as an expert in rhetoric who devoted more than a third of his Art of Rhetoric to study of the audience. Ever since, rhetoricians have taught that a speaker who would persuade others to believe and to act must understand how the listeners feel, what they want, and what they need. In short, the speaker must begin where his or her listeners are. A persuasive writing or speaking is often aimed at the heart or the stomach instead of the head. This can mean that there are some things or reasons more acceptable to the readers or listeners’ feeling, which is in the stomach, than to their logic, which is in the head. Consequently, instead of being logical only, a persuasive writer or a speaker might add some strategies in order to win the readers or listeners’ assent.